Ataxia telangiectasia: evolução da escala SARA (Scale for the Assessment and Rating of Ataxia) com força de preensão palmar e força muscular inspiratória - Trajano, Karina Kakiuchi [UNIFESP] (2019)
Ataxia Telangiectasia (A-T) is a rare, hereditary, non-raceable, neurodegenerative disease that affects both sexes. It results from the ATM mutation (ataxiatelangiectasia, mutated) on chromosome 11q22-23. The clinical presentation is progressive and debilitating with evidenced motor impairment. Objective: To evaluate the evolution of motor function, palmar grip strength, and respiratory muscle strength in patients with ataxia telangiectasia. Methods: This was a longitudinal study in which 24 patients (children, adolescents and adults) with A-T diagnosis were evaluated. The Scale for the Assessment and Rating of Ataxia (SARA) scale which assess posture, gait, balance, coordination and speech was used for motor assessment. The score ranges from 0 to 40, the higher the severity of ataxia. Palmar grip strength was assessed as a measure of peripheral muscle strength with the analog dynamometer. The inspiratory pressure (PiMáx) and expiratory pressure (PeMáx) maxims were used to measure respiratory muscle strength by using the manovacuometer. Pulmonary function was assessed by spirometry according to recommendations, with the following outcomes: forced vital capacity (FVC), forced expiratory volume on the first second (FEV1), relationship between (FEV1/FVC) and forced expiratory flow (FEF). All evaluations mentioned were repeated every three months for a year, totaling four evaluations. Patients were questioned about the history of disease and performance and / or follow-up of physical therapy during the study months. Results: of the total number of volunteers, 17 (71%) were males, mean age 13 years  7.6 years, symptoms onset at 1.3 years (1 month - 4 years of life) and telangiectasia at 3.3 years (1 month up to 10 years of life); who were diagnosed at 4.7 years (1-11 years). Of the total number of patients, 14 (58%) underwent supervised physiotherapy and the others, unsupervised physical therapy. There was no change at SARA scale at baseline (19.5 +/- 9.7 – 21.7) at the end of the protocol (18.5 +/- 9.7 – 22.0), p = 0.72. No change in palmar grip values (12.1 ± 5.5 kg) was observed for the final (12.4 ± 6.1 kg), p = 0.79. PiMax increased over the course of 12 months, initial 69.1 +/- 26.6 cmH2O vs final 83.1 +/- 29,6 cmH2O, p = 0.03, in the same manner as PeMax of 50.5 +/- 14.8 cmH2O to 58.9 +/- 29.6 cmH 2 O final, p = 0.04. Conclusions: Although A-T is a degenerative and progressive disease, no motor worsening and muscular strength peripheral were observed over 12 months, and respiratory muscle strength showed significant improvement.